Diseminasi Kebijakan Pemerintah dalam Upaya Penurunan Prevalensi Stunting melalui Pendekatan Health Communication Model di Kabupaten Aceh Barat - Kesha, Cut Nabilla; Maulida, Desi; Maryam, Maryam; Safrida, Safrida (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
West Aceh Regency has been designated as one of the focus locations for integrated stunting reduction interventions in 2022 based on the Decree of the Minister of National Development Planning/Bappenas. In 2022, West Aceh Regency recorded 610 children suffering from stunting spread across 11 of 12 sub-districts. Among the causes of high stunting is that the community is not provided with reliable information about stunting, and there are no specific regulations governing stunting prevention as a preventive measure at the district level. The research was conducted in two sub-districts, namely Johan Pahlawan Sub-district and Bubon Sub-district, which are the sub-districts with the most stunting sufferers out of 10 other sub-districts. This research aims to describe the dissemination of the implementation of stunting prevention policies along with the strategic steps taken in efforts to reduce stunting. The method used in this research is descriptive qualitative with data collection through interviews, observation and documentation. The results of the research show that policy implementation in an effort to reduce the prevalence of stunting in West Aceh Regency can be said to have run optimally. The strategic efforts undertaken to achieve the goal of reducing stunting prevalence begin with identifying problems, identifying target audiences, formulating educational messages, utilizing information media, intervention strategies through programs to accelerate stunting reduction, determining priority groups and using implementation methods by coordinating with stakeholders.